Detailed investigation of methylmercury accumulation in rice grain from Hg2+-spiked non-contaminated paddy field soils. (May 2020) - Kodamatani, Hitoshi; Daiba, Yuri; Morisaki, Shintarou; Ichitani, Katsuyuki; Kanzaki, Ryo; Tomiyasu, Takashi
Abstract: Total-Hg (T-Hg) and methylmercury (MeHg) concentrations in rice grains were measured to understand the MeHg accumulation process. Rice plants were cultivated in Hg 2+ -spiked non-contaminated soils in experimental pots at three different places. Although soil MeHg concentrations in the pots changed significantly and individually during the rice-growing season, T-Hg concentration of brown rice grain was high at high soil MeHg concentration. In addition, there was no significant variation in T-Hg concentration in brown rice grains from individual panicles or among panicles obtained from the same pot, although the period of growth for each panicle was different. The highest T-Hg concentration of brown rice grains recorded for a panicle was 1.4 ± 0.1 mg kg −1 (n = 8), and the corresponding MeHg ratio was 76%. In addition, the T-Hg and MeHg concentrations in various parts of the brown rice grain—white rice (endosperm), bran, and embryo—were measured. Among the parts of the brown rice grain, the embryo had the highest Hg concentration. Furthermore, Hg concentration in the grain was constant during grain filling. These findings suggest that MeHg formed in soil accumulates in the rice plant during growth and is supplied to the rice grains continuously for the entire duration of the grain development period. Highlights: Hg and MeHg levels in rice were studied to clarify the MeHg accumulation process. Individual panicles did not differ significantly in total Hg concentrations. Hg concentration of brown rice was over 1 mg kg −1 at 10 mg kg −1 spiked Hg 2+ in soil. Of the parts of the rice grain, the embryo had the highest Hg concentration. The findings suggest that MeHg is supplied to grains throughout grain development.